Upaya Pencegahan dan Perawatan Hipertensi di Rumah Melalui Media Pembelajaran Bagi Masyarakat di Kabupaten Pangandaran - Nuraeni, Aan; Mirwanti, Ristina; Anna, Anastasia (BAGIMU NEGERI : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2018)
Hypertension is a health problem that needs attention in Indonesia. To decrease the incidence of hypertension, we could give health education to the community. Provision of information and education through learning media such as booklet was one effort to empower the community in preventing and performing hypertension treatment at home. Increasing health promotion through the provision of information and education using learning media was expected to improve the knowledge and self-efficacy of the community that will affect the behavior of the community. Pangandaran Regency is one of the target areas of Padjadjaran University where hypertension is one of the highest prevalence diseases. The purpose of this activity was to improve knowledge of community self-efficacy about prevention and treatment of hypertension. This activity was carried out from community surveys, booklet preparation, booklet socialization, and evaluation. At the implementation stage, the activity was followed by 22 people and 13 of them had hypertension. People who had hypertension were given hypertension management booklet then their knowledge and self-efficacy evaluate after one to two weeks. The result showed that there was an increase in the average knowledge and self-efficacy of them after the program.Â Besides that, there were differences in an average score of public knowledge before and after the giving of booklets, but there was no difference in the average self-efficacy score. This booklet can be used to provide health education to the community related to prevention and treatment of hypertension, so hopefully, there will be changes in behavior to manage hypertension.Keywords: Booklet, learning media, hypertension, knowledge, self-efficacy